The Influence of Social Media Marketing on Patient Visit Intention Mediated by Brand Awareness - Tita Hariyanti; Gladys Kurniawan; Achmad Yunus; Dwi Saputro; Unix Cahya Husada; Catharina Louise Rhynanti; Fatchur Rohman (Universitas Muhammadiyah Yogyakarta, 2023)
Social media marketing can increase consumer awareness and recognition of a brand (brand awareness) from a product or service. Brand awareness can ultimately influence the formation of consumer visit intentions for these products and services. RSU Universitas Muhammadiyah Malang (RSU UMM) is one of the Type C general hospitals conducting social media marketing since 2018. This study aims to determine the effect of social media marketing on the visit intention of patients at the hospital. The research was conducted with a quantitative observational method in a cross-sectional study using a questionnaire through Google Forms. The research sample was 96 people who were loyal consumers (followers) of the social media accounts (Facebook, Instagram, and Twitter) of the RSU UMM. Data analysis was carried out by using Partial Least Square (PLS). The findings showed a positive and significant influence of social media marketing on the patient's visit intention, mediated by the patient's brand awareness. This research concluded that RSU UMM's social media marketing efforts positively and significantly affected patient visit intentions and strengthened by the influence of brand awareness. Therefore, RSU UMM must improve its marketing strategy, primarily through social media marketing.